The Trail Smelter Case Re-examined: Examining the Development of National Procedural Mechanisms to Resolve a Trail Smelter Type Dispute - Kerkhof, van de, Martijn (Utrecht Journal of International and European Law, 2011)
This article re-examines the iconic Trail Smelter dispute. The article discusses the way a modern day Trail Smelter type dispute would be dealt with in the current time. The article examines the opportunities of resolving such a dispute using national mechanisms. Consequently, the United States and Canadian courts are examined in terms of their applicability to a modern day Trail Smelter type dispute. The classic obstacles that prevented access to these courts in the original Trail Smelter dispute are described, subsequently the current status of these obstacles is assessed. The evaluation indicates that the national mechanisms to deal with a Trail Smelter type dispute have gone through a pro- nounced development. Whereas Canadian courts are still reluctant to exercise their jurisdiction extraterritorially, recent legislation seems to indicate that in the present day a Trail Smelter dispute could potentially fall within the jurisdiction of a United States court. Overall the thesis indicates that national mechanisms have started to fill the void that is left by the lack of decisive action that can be taken using international mechanisms. The current situation shows an increasing willingness to provide opportunities for resolving transboundary disputes at the private party level.